Employee Well Being terhadap Unit Bumi Kepanduan Sentul - Siti Nurhasanah; Erni Yuningsih (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
Employee well-being has become an important issue in human resource management, as it is closely related to employees’ motivation, service quality, and overall organizational performance. In practice, however, many organizations have not fully implemented employee welfare policies in a consistent and sustainable manner. This study aims to analyze the impact of employee well-being on employee performance at Bumi Kepanduan Sentul Bogor, an edu-adventure camping ground managed by PT Pandu Bina Sejahtera. The research employed a descriptive qualitative approach through Field Work Practice (Kuliah Kerja Lapangan/KKL). Data were collected through direct observation, in-depth interviews with employees and management, and group discussions conducted during field activities. The findings show that employee well-being, particularly psychological well-being and work motivation, has a close relationship with service quality and the achievement of visitor targets. Periods of improved employee well-being were characterized by higher motivation, better work comfort, and more effective service delivery, which positively contributed to organizational performance. Although the company has implemented several initiatives, such as gradual wage adjustments, digital attendance systems, and the provision of work facilities, these efforts have not yet fully addressed employees’ needs. Therefore, more consistent and comprehensive employee well-being policies are required to support sustainable performance improvement.